Throughout in vitro first spermatogenic wave: Next-generation sequencing gene expression patterns of fresh and cryopreserved prepubertal mice testicular tissue explants - Dumont, Ludovic; Lopez Maestre, Hélène; Chalmel, Frédéric; Huber, Louise; Rives-Feraille, Aurélie; Moutard, Laura; Bateux, Frédérique; Rondanino, Christine; Rives, Nathalie (Frontiers in Endocrinology, 2023)
Suitable cryopreservation procedures of pre-pubertal testicular tissue associated with efficient culture conditions are crucial in the fields of fertility preservation and restoration. In vitro spermatogenesis remains a challenging technical procedure to undergo a complete spermatogenesis. The present work first shows that cryopreservation had very little impact on gene expression in testicular tissue, either directly after thawing or after 30 days in culture. Thereafter, transcriptomic analyses reveal that cultured tissues expression profiles are almost comparable between D16 and D30; highlighting an abnormal kinetic throughout the second half of the first spermatogenesis during in vitro cultures. In addition, testicular explants have shown dysregulation of their transcriptomic profile compared to controls with genes related to inflammation response, insulin-like growth factor and genes involved in steroidogenesis. Transcriptomic analysis of testis tissue samples is highly informative due to the large number of expressed genes and identified isoforms. This study provides a very valuable basis for future studies concerning in vitro spermatogenesis in mice.